2016
DOI: 10.5624/isd.2016.46.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori registration and subtraction of periapical radiographs for the evaluation of external apical root resorption after orthodontic treatment

Abstract: PurposeThis study employed a posteriori registration and subtraction of radiographic images to quantify the apical root resorption in maxillary permanent central incisors after orthodontic treatment, and assessed whether the external apical root resorption (EARR) was related to a range of parameters involved in the treatment.Materials and MethodsA sample of 79 patients (mean age, 13.5±2.2 years) with no history of trauma or endodontic treatment of the maxillary permanent central incisors was selected. Periapic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Current samples included cases treated with aligners without relation to conventional fixed appliance cases, however other studies conducted on root resorption following orthodontic treatment with fixed conventional appliance proved compatible results. In our study, 72% of the teeth demonstrated root resorption, in agreement with a study done by Handem et al (2016) that stated root resorption will accompany fixed conventional orthodontic treatment in 50.3% of the cases, whilst according to Kreich et al (2016) all patient demonstrated a degree of root resorption on different scales. In a comparison done in 2017 by Iglesias-Linares et al (2017) concluded that patients treated with fixed conventional orthodontic treatment were as half as less susceptible to EARR compared to patients treated with removable aligners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Current samples included cases treated with aligners without relation to conventional fixed appliance cases, however other studies conducted on root resorption following orthodontic treatment with fixed conventional appliance proved compatible results. In our study, 72% of the teeth demonstrated root resorption, in agreement with a study done by Handem et al (2016) that stated root resorption will accompany fixed conventional orthodontic treatment in 50.3% of the cases, whilst according to Kreich et al (2016) all patient demonstrated a degree of root resorption on different scales. In a comparison done in 2017 by Iglesias-Linares et al (2017) concluded that patients treated with fixed conventional orthodontic treatment were as half as less susceptible to EARR compared to patients treated with removable aligners.…”
Section: Discussionsupporting
confidence: 92%
“…This study was not directed towards data differentiation on the bases of gender nor age, since previous studies reported that gender and age have no statistical significance when it comes to root resorption incidence (Iglesias-Linares et al, 2017;Kreich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%